TRANSLATION PROBLEMS OF SOME IDIOMS RELATED TO BUSINESS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article aims to investigate what difficulties arise in the two processes of interpreting and translating idioms and fixed expressions from one language into another. An attempt has been made to exemplify the difficulties and strategies regarding this phenomenon so that a pseudo-descriptive list of existing difficulties might be declared for the readers and translators of such expressions.